Magdalenian and Epimagdalenian chronology and palaeoenvironments at Kůlna Cave, Moravia, Czech Republic - Reade, Hazel; Grimm, Sonja B; Tripp, Jennifer A; Neruda, Petr; Nerudová, Zdeňka; Roblíčková, Martina; Sayle, Kerry L; Kearney, Rebecca; Brown, Samantha; Douka, Katerina; Higham, Thomas F G; Stevens, Rhiannon E (Archaeological and anthropological sciences, 2021)
UNLABELLED: Kůlna Cave is the only site in Moravia, Czech Republic, from which large assemblages of both Magdalenian and Epimagdalenian archaeological materials have been excavated from relatively secure stratified deposits. The site therefore offers the unrivalled opportunity to explore the relationship between these two archaeological phases. In this study, we undertake radiocarbon, stable isotope (carbon, nitrogen and sulphur), and ZooMS analysis of the archaeological faunal assemblage to explore the chronological and environmental context of the Magdalenian and Epimagdalenian deposits. Our results show that the Magdalenian and Epimagdalenian deposits can be understood as discrete units from one another, dating to the Late Glacial between c. 15,630 cal. BP and 14,610 cal. BP, and c. 14,140 cal. BP and 12,680 cal. BP, respectively. Stable isotope results (δ13C, δ15N, δ34S) indicate that Magdalenian and Epimagdalenian activity at Kůlna Cave occurred in very different environmental settings. Magdalenian occupation took place within a nutrient-poor landscape that was experiencing rapid changes to environmental moisture, potentially linked to permafrost thaw. In contrast, Epimagdalenian occupation occurred in a relatively stable, temperate environment composed of a mosaic of woodland and grassland habitats. The potential chronological gap between the two phases, and their associations with very different environmental conditions, calls into question whether the Epimagdalenian should be seen as a local, gradual development of the Magdalenian. It also raises the question of whether the gap in occupation at Kůlna Cave could represent a change in settlement dynamics and/or behavioural adaptations to changing environmental conditions. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s12520-020-01254-4.
Keywords: Late Upper Palaeolithic; Carbon isotopes; Permafrost; Final Palaeolithic; Sulphur isotopes; Nitrogen isotopes